Deoxygenation-enhanced chemical looping gasification: a new pathway to produce hydrogen from biomass. Issue 6 (9th March 2022) - Sun, Zhao; Liu, Hanpeng; Toan, Sam; Shi, Weizhi; Cheng, Dongfang; Sun, Zhiqiang
Abstract : A new pathway to produce hydrogen from biomass is proposed: deoxygenation-enhanced chemical looping gasification. Abstract : Biomass to hydrogen production has been regarded as a potential approach for green hydrogen synthesis. However, carbon dioxide and bio-tar are inevitably produced, which critically restricts the refinement of biomass-derived syngas. In this study, deoxygenation-enhanced chemical looping biomass gasification (DE-CLBG) is proposed for hydrogen-rich syngas production together with CO2 /H2 O deoxygenation and catalytic bio-tar removal using the composite Fe/CaO as the deoxidizer. The DE-CLBG process is comprised of a deoxygenated gasification stage and a regeneration stage. During the deoxygenated gasification stage, the deoxidizer is converted under steam gasification via CaO + Fe + O 2− → Ca2 Fe2 O5 with biochar generation; at the regeneration stage, biochar is further gasified with the achievement of deoxidizer reduction via Ca2 Fe2 O5 + C → CaO + Fe + CO x . Experimental results show that the hydrogen production and maximum concentration upon applying 0.300 g of deoxidizer per g of biomass are 6.70 mmol and 89.61 vol%, which was increased by 287% and 27%, respectively, compared with the non-deoxygenated process. Results from the Mössbauer spectrum show that Fe 0 is finally transformed into Fe 3+ in the form of Ca2 Fe2 O5 and a small amount of Fe3 O4, corresponding to the deoxygenation efficiency of 99.21%. The NMR results imply that aromatic carbon is the main form in biochar whether introducing deoxidizer or not, and deoxygenation can promote the removal of O -alkyl C.